2017
DOI: 10.1016/j.physbeh.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The visible burrow system: A view from across the hall

Abstract: The visible burrow system (VBS) is an ethologically relevant social stress model that creates a distinct dominance hierarchy in rats. Randall Sakai’s laboratory performed an impressive series of studies documenting the very different impact of VBS exposure on the brain and behavior of dominants (DOM) and subordinates (SUBs). Hierarchy formation causes pronounced changes in metabolism in SUBs relative to both DOMs and unstressed controls, resulting in marked weight loss and metabolic imbalance. Stress testing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Further, relative to dominants, subordinate males generally show elevated baseline corticosterone and adrenal hypertrophy coupled with reduced levels of corticotropin binding globulin (CBG) indicating higher levels of free corticosterone (Spencer et al, 1996), thymic atrophy and reduced body weights (McEwen et al, 2015;Tamashiro et al, 2005). These physiological outcomes are consistent with other chronic stress exposures such as chronic variable stress (CVS) (Herman and Tamashiro, 2017;McEwen et al, 2015). However, it should be noted that these differences are not found in all VBS studies, suggesting that social contexts between VBS colonies may vary and influence physiological outcomes (Buwalda et al, 2017;Dijkstra et al, 1992;Kozorovitskiy and Gould, 2004;McEwen et al, 2015).…”
Section: Stress Responsivity In Vbs Housed Mice and Ratssupporting
confidence: 52%
See 1 more Smart Citation
“…Further, relative to dominants, subordinate males generally show elevated baseline corticosterone and adrenal hypertrophy coupled with reduced levels of corticotropin binding globulin (CBG) indicating higher levels of free corticosterone (Spencer et al, 1996), thymic atrophy and reduced body weights (McEwen et al, 2015;Tamashiro et al, 2005). These physiological outcomes are consistent with other chronic stress exposures such as chronic variable stress (CVS) (Herman and Tamashiro, 2017;McEwen et al, 2015). However, it should be noted that these differences are not found in all VBS studies, suggesting that social contexts between VBS colonies may vary and influence physiological outcomes (Buwalda et al, 2017;Dijkstra et al, 1992;Kozorovitskiy and Gould, 2004;McEwen et al, 2015).…”
Section: Stress Responsivity In Vbs Housed Mice and Ratssupporting
confidence: 52%
“…Unlike several stress paradigms that emphasize controlled exposures to known stressors (e.g. restraint stress, chronic variable stress, social defeat stress) (Herman and Tamashiro, 2017), clearly the social stress exposure from living in VBS is not equivalent for all individuals. Depending upon the social context (e.g.…”
Section: Individual Differences In Stress Responsivity In Groupsmentioning
confidence: 94%
“…1B), where victims are housed in continuous close, visual and olfactory contact with neighboring attackers which makes this more a chronic social stress model with a dominant and a subordinate animal [35,36]. The third variant is also making use of hierarchical dominance contexts where chronic social stress of subordination is studied in hierarchical colony structures such as the visible burrow system [37][38][39] (Fig. 1C).…”
Section: Responses To Social Stress In Animalsmentioning
confidence: 99%
“…Multiple factors may be causal in volumetric changes such as structural remodeling, neuro-and gliogenesis and apoptosis [29,63,64]. Social stress paradigms such as psychosocial stress in the resident-intruder paradigm and chronic stress of subordination in the visible burrow system in several animal models showed dendritic atrophy in CA1 and CA3 pyramidal neurons that persisted even after prolonged stress free recovery periods [39,41,65,66]. Somewhat surprisingly, dendritic atrophy in CA3 neurons was not only observed in animals exposed to chronic social stress but also observed in rats that were socially dominant in social colony structures like the visible burrow system [65] which may indicate that maintaining social dominance can be a source of chronic social stress.…”
Section: Hippocampusmentioning
confidence: 99%
“…58,81 The variation in body weight and HPA status among mixedsex group-housed rats in visible burrow systems shows that individual animals respond differently in a social situation depending on their social status and that the animals in the group can become to some extent physiologically distinct. 10,11,32 This basic conclusion has been corroborated in several studies of commonly-used laboratory strains of rats or mice in studies comparing individual and group housing: glucocorticoid levels are either the same or lower in singly housed animals, 7,33,35,42,45 despite some differences related to strains and housing density. 63,89 One study showed that after separation of group-housed female mice, the concentration of FCM decreased from day 1 to day 3 after separation and stabilized at these lower concentrations during days 4 to 7, suggesting an adaptation to individual housing that was associated with lower HPA reactivity.…”
Section: Examples Of Allostasis and Resiliencementioning
confidence: 68%